An Interpretive Inquiry Into Middle School Curriculum - Guiver, Gary Thomas (Curtin University, 2003)
This thesis is an interpretive inquiry which focuses on the curricular elements of a middle school program. The research project is based on the data collected from two specific classes and from five particular teachers, during the implementation phase of a middle school program. The research makes use of multiple methodologies including an empirical study, narrative accounts by teachers and students, interviews, autobiographical and biographical material, and notes from a personal journal. It was intended that the thesis create a detailed, multi-dimensional, image of the school curriculum. Common threads evident in the data obtained from the teachers indicated that there was an element of uncertainty regarding expectations for the middle school program, a perception that there was conflict over resources, a belief that disputes about curriculum `ownership' had impacted negatively on the program, and a degree of disappointment that the program's potential had not been fulfilled. Despite these constraints, all the teachers noted high levels of professional satisfaction and a sense of collegiality within the middle school team. The students did not express any particular preferences regarding curriculum content, but were principally concerned about the social environment within their own homegroup class and within the wider school community. A significant proportion of the students sampled commented positively on the relationships that they had developed with their peers and teachers. The findings appear to indicate that, provided that the class work is of some relevance and interest, young adolescent students are more concerned about who their teacher might be, rather than what they might actually teach.The tensions that are inherent in the debate about the curriculum and who owns it are identified as difficulties that teachers and administrators need to address if new middle school programs are to be successfully implemented. It is a genuine issue that concerns teachers and schools, therefore, efforts should be made to find ways to ensure that debate about the curriculum takes place within an educational framework which, initially, is separate from any discussion regarding the management and allocation of resources. It might also be helpful if the debate were, in some way, held in `neutral territory', and not viewed as a matter of choice between a traditionally conservative curriculum and a radically progressive one, but perhaps something else. The thesis concludes with a suggestion that Surrealism might be used as a device by which the integrity of the subjects, found in a traditional curriculum, may be preserved in a structure that still allows for the rich and, perhaps, the strange possibilities of an integrated program. It could be seen as a recombination or different combination of disciplines which may create a more interesting whole, however, it would still be recognizable or, at least, its components would be. Reference is made to one particular painting by Rene Magritte, "Time Transfixed" as a means of illustrating this proposition.